ANALISIS TEOLOGIS TENTANG PENGGUNAAN KATA “MENYESAL” PADA DIRI ALLAH - Julitinus Harefa (Manna Rafflesia, 2023)
The word "repent" in God draws various interpretations and impacts the concept of God's immoral nature, which cannot be changed or fixed. So, there are members of Christian congregations outside of Christianity who conclude that God is imperfect and not omniscient. The word regret, in its general sense, always has a negative meaning, where the word regret is related to the feeling felt when one realizes that something has been done that has hurt someone and hopes to take it back. At such a level of understanding, God cannot identify with sinful human character. Therefore, the author examines the use of the word through theological analysis with a qualitative approach using literature/literature studies. The goal is to find out how to interpret the word "repentance" attached to God. Then, knowing the translation used has represented the real meaning. Then, the author looks for the use of the word "regret" in the general sense and theology. In conclusion, God can't have feelings caused by sin so that He regrets and causes His nature and character to change because of the behavior of His creation.